The Influence of Parenting Styles and Students' Interest in Learning on Student Learning Outcomes in Creative Products Entrepreneurship Class XII Private Vocational School Preparation Pematang Siantar - Mei Siagian (International Journal of Integrated Science and Technology, 2023)
This research aims to gain knowledge regarding the influence of parental parenting patterns and students' interest in learning on student learning outcomes in PKK subjects at the Pematang Siantar Preparatory Private Vocational School.This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 124 people, and the sample used was 124 people. The sample collection technique used was the total sample. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2).The results of this study state that: 1) there is a positive influence of parental parenting patterns on student learning outcomes, this result can be seen in the t test where the t value of parental parenting patterns (3.949) > t table value (1.979). 2) there is a positive and significant influence of student interest in learning on student learning outcomes, this result can be seen in the t test where the t value of student interest in learning (7.998) > t table value (1.979) which means that this variable is significant. 3) parenting patterns and students' interest in learning together influence student learning outcomes, these results can be seen in the F test where the Fcount value (319, 984) > Ftable value (3.07). The R square coefficient of determination test was found to be 0.841, which means that 84.1% of the variables of parental parenting and student interest in learning were on student learning outcomes in the Creative Entrepreneurship Products (PKK) class XII Pematang Siantar Preparatory Private Vocational School, and 15.9% was the influence of other variables not examined in this research.